ST.MM: PENGUKURAN PRODUKTIVITAS PADA PRODUKSI ROTI MENGGUNAKAN METODE OMAX DI UD ROTI SPECIAL - wahyu madeali; Junaenah Junaenah (JURNAL INDUSTRI DAN TEKNOLOGI SAMAWA, 2022)
Roti Special is a family factory that manufactures and sells various types of sandwiches and plain breads to meet customer needs. And to measure the company's productivity using the OMAX method. The research data is secondary data on bread production which was taken for six months from December 2021 to May 2022. The results of data collection were analyzed using the Objective Matix (OMAX) method. OMAX is a partial productivity measurement system developed to monitor productivity in every part of the company by productivity criteria in accordance with the existence of the section. By using the traffic light system, it will be obtained which indicators are often at a poor level. Based on the analysis that has been carried out, the productivity index throughout 2022 has fluctuated. The highest productivity index was achieved in April of 5.728% and the lowest was in January of 0.375%. From the results of the analysis using the OMAX method, it is found that indicator 2 is often at a low point, namely labor hours and raw materials, through fault tree analysis, it is known that the causes that affect the use of working hours and machine hours. Proposed improvements given through this research include: making a procedure that regulates the operator in setting the machine, and making changes in the machine maintenance system to support the preventive maintenance that has been determined, namely by carrying out machine maintenance before the production process takes place.